Asymmetric Synthesis of Nature‐Inspired Bioactive Spiro Compounds through Organocatalytic Diels–Alder Reactions. Issue 6 (21st April 2016) - Ramachary, Dhevalapally B.; Krishna, Patoju M.
Abstract: An asymmetric organocatalytic arylideneacetone–olefin [4+2] cycloaddition reaction of a variety of arylideneacetones and 1, 3‐indandione with different aldehydes is reported in toluene at ambient conditions to furnish the optically pure spiro compounds, which are further converted into medicinally useful spiromentins by the Suzuki reaction. This asymmetric reaction has advantageous features such as high rate and selectivity, uses easily available substrates/catalysts, has many synthetic/medicinal applications, and gives excellent yields for generating a vast library of chiral spiro compounds. Abstract : I spi with my little tri : An asymmetric organocatalytic arylideneacetone–olefin [4+2] cycloaddition reaction of arylideneacetones and 1, 3‐indandione with different aldehydes in ambient conditions is described. The reaction yielded optically pure spirotriones, which were further converted into medicinally useful spiromentins by the Suzuki reaction.